Analisis Penetapan Harga Pokok Produksi dalam Menentukan Harga Jual Produk Kopi di Toko Sarah Jaya Rantepao - Grace Sriati Mengga; Silva Pasamba; Yohanis L. Ta’dung (Universitas Kristen Indonesia Toraja, 2025)
This study aims to determine the cost of coffee production as a basis for setting the selling price in the Sarah Jaya coffee business. Accurate calculation of production costs is essential because it directly affects pricing decisions and the level of profit generated by the business. The full costing method is used to determine the cost of production, as this method provides a more comprehensive and detailed calculation by including all cost components required in the production process, such as raw material costs, direct labor costs, and both fixed and variable manufacturing Overhead costs. Determining the cost of production using an appropriate method can significantly influence the determination of the selling price and ensure that the business achieves sustainable profitability. The application of the full costing method is expected to provide practical benefits for Small and Medium Enterprises (MSMEs), particularly in improving financial management and decision-making accuracy. The results of this study indicate that the calculation of the cost of production for the Sarah Jaya coffee business conducted by the business owner using the full costing method aligns well with the determination of the selling price and the profit generated. This is because the full costing method takes into account more detailed and comprehensive cost elements, resulting in a more realistic and reliable calculation of production costs.